Utilization of Coal Bottom Ash a Low-Cost Adsorbent for the Removal Acid Red 114 Dye - Kuntari Kuntari; Nurul Hidayat Aprilita; Suherman Suherman (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
A research about adsorption of acid red 114 using coal bottom ash has been conducted. This research was aimed to examine the ability of coal bottom ash in acid red 114 adsorption. Some adsorption parameters i.e. dosage adsorbent, contact time and pH medium were examined in the adsorption processes. The characterization of coal bottom ash was determined using X-Ray Diffraction. Acid red 114 concentration is measured by using UV-Visible spectrophotometer. The adsorption percentage of acid red 114 on the coal bottom ash is 91.2% at pH 1.5; contact time 80 min, acid red 114 concentration 10 mg/L for every 1.5 g bottom ash.